2013
DOI: 10.4236/ojped.2013.34057
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between obesity and gastroesophageal reflux disease (GERD) in a pediatric cohort

Abstract: Objectives: Previous reports correlating obesity with gastroesophageal reflux disease (GERD) in children have yielded conflicting results. This study examined whether increasing BMI (body mass index) correlated with increasing grades of endoscopic and/or histopathologic GERD in a cohort of inner city children. Designs and Methods: 340 consecutive children (1-18 years) were classified as obese (BMI > 95%) for age and gender. Both endoscopic findings and esophageal histopathology were characterized by graded adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…6 The results of the analysis in this study which showed the absence of a relationship between BMI and GERD were in line with the cohort study conducted at the State University of New York in New York, USA which concluded that there was no relationship between BMI and GERD obtained from BMI testing with GERD endoscopic results with a p-value of 0.75 and from the results of BMI testing with a degree of GERD histopathological abnormality with a p-value of 0.16. 9 The same results were also found in a study at Sriwijaya University, Palembang, Indonesia with a regression test and found a relationship between obesity and GERD with a p-value of 0.001, but no relationship was found between overweight and GERD with a p-value of 0.988. This shows that increased BMI is not an independent risk factor of GERD.…”
Section: Discussionsupporting
confidence: 71%
“…6 The results of the analysis in this study which showed the absence of a relationship between BMI and GERD were in line with the cohort study conducted at the State University of New York in New York, USA which concluded that there was no relationship between BMI and GERD obtained from BMI testing with GERD endoscopic results with a p-value of 0.75 and from the results of BMI testing with a degree of GERD histopathological abnormality with a p-value of 0.16. 9 The same results were also found in a study at Sriwijaya University, Palembang, Indonesia with a regression test and found a relationship between obesity and GERD with a p-value of 0.001, but no relationship was found between overweight and GERD with a p-value of 0.988. This shows that increased BMI is not an independent risk factor of GERD.…”
Section: Discussionsupporting
confidence: 71%